Dr. Aurelio Diaz- Ufano Peral : Smith New Surgery in Peru. Semblance - Heraud Larrañaga, José (1997)
The December 10, 1928 a young medical student put the glossed lines at the beginning of a monograph entitled " Histological study of Biliary Tract ." Surprising as only 19 years old, exposed to both balance, depth and maturity , concepts that are a code of life : sincerity , honest effort , commitment and care and of course great modesty . The student was Aurelio Diaz Ufano Peral, who already in this work, evident of the qualities that would make him an outstanding surgeon and Professor of Surgery . Under the guidance of Dr. Daniel Mackehenie , who is recognized as the distinguished teacher , published the following year : " Contribution to the Study of Leukocyte oxidásicos Beads " , in Annals Hospital , Monthly Journal of Medicine and Surgery , prepared by professionals who served in the various institutes Assistance Public Welfare Society of Lima. The same study is required by the Argentine and returned colleagues publish the September 14, 1931 , in " The Doctor Day" of Buenos Aires.